2011
DOI: 10.3892/or.2011.1464
|View full text |Cite
|
Sign up to set email alerts
|

Role of autophagy in resistance to oxaliplatin in hepatocellular carcinoma cells

Abstract: Abstract. In spite of an initially promising anti-tumor activity, oxaliplatin-based combinatorial treatments can eventually result in a tumor resistance response. In this study we aimed to understand the role of autophagy in HCC cell resistance to oxaliplatin and to discuss its potential therapeutic implication. We found that exposure to oxaliplatin induced a significant increase in LC3 lipidation and subsequent LC3 puncta formation. While the proliferation of HCC cells was inhibited upon oxaliplatin exposure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…Acridine orange staining of live HepG2 and Hep3B cells showed increased AVO formation following SAMe pre-treatment (Figure 3A). Consistent with our previous results [4], I/H exposure increased AVOs amount in both HepG2 and Hep3B cells. Acute I/H with SAMe pre-treatment had no apparent influence on AVO formation in Hep3B cells, while a notable increase in AVOs was observed in HepG2 cells.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Acridine orange staining of live HepG2 and Hep3B cells showed increased AVO formation following SAMe pre-treatment (Figure 3A). Consistent with our previous results [4], I/H exposure increased AVOs amount in both HepG2 and Hep3B cells. Acute I/H with SAMe pre-treatment had no apparent influence on AVO formation in Hep3B cells, while a notable increase in AVOs was observed in HepG2 cells.…”
Section: Resultssupporting
confidence: 93%
“…Despite recent progress in diagnostic and therapeutic management, hepatocellular carcinoma (HCC) patient prognosis remains poor [14]. The level of downregulation of growth arrest DNA damage-inducible gene 45β (GADD45b) in HCC is strongly correlated with increased tumor malignancy [5].…”
Section: Introductionmentioning
confidence: 99%
“…In oesophageal cancer cell, autophagy can promote these drug-resistant cancer cell survival and recovery following treatment with chemotherapeutics (18). In addition, autophagy may function importantly in HepG2 cell resistance to oxaliplatin and the resistance could be recovered apparently by inhibition of autophagy (19). Therefore, these results have indicated that autophagy may play an important role in the mechanism of the tumour cells resistant to anti-cancer drugs.…”
Section: Background and Evidencementioning
confidence: 91%
“…These facts indicate that this enzyme could have an important role in resistance acquisition processes to different chemotherapeutic drugs. Furthermore, it has been shown that some of the PKM2 biological functions depend on the enzyme’s nuclear translocation which is promoted by different post-translational modifications such as tyrosine phosphorylation [ 15 17 ], lysine acetylation [ 18 ], or sumoylation [ 19 ] in response to the factors EGFR [ 20 ], IL-3 [ 21 ] or Oct-4 [ 22 ] respectively. While in the majority of the above mentioned cases PKM2 translocation results in the stimulation of cell proliferation, it has been demonstrated that after other kinds of stimuli like DNA damage or oxidative stress, PKM2 translocates to the nucleus of cells leading to the activation of cell death in a caspases and Bcl-2 independent manner [ 23 ].…”
Section: Introductionmentioning
confidence: 99%